PERAN PEMANGKU KEPENTINGAN SEBAGAI UPAYA PENGEMBANGAN PARIWISATA DI KABUPATEN BIAK NUMFOR - Yustisia Kristiana; Theodosia C. Nathalia (Jurnal Pariwisata Pesona, 2019)
Tourism development in Biak Numfor Regency is inseparable from the role of stakeholders. Tourism management has been developed in Biak Numfor Regency, but has not shown results. This is influenced by the not yet optimal management of tourism destinations. This study aims to identify tourism stakeholders in the Biak Numfor Regency, find out the role of tourism stakeholders in Biak Numfor Regency, and examine the needs of tourism stakeholders in Biak Numfor Regency. The primary data collection technique is done through interviews and observations. Interviews were conducted with tourism stakeholders in Biak Numfor Regency. Respondents who are stakeholders are selected by purposive sampling and snowball sampling methods. Data obtained were analyzed using stakeholder analysis and needs analysis. The results showed that there were 16 tourism stakeholders in Biak Numfor Regency and most of them served as subjects, namely stakeholders who had high interests but low influence. Needs needed by tourism stakeholders in Biak Numfor Regency, i.e. (1) understanding of tourism destination governance; (2) coordination between tourism stakeholders; (3) the synergy of tourism development programs in Biak Numfor Regency; and (4) ongoing assistance.